Biochar and organic fertilizer drive the bacterial community to improve the productivity and quality of Sophora tonkinensis in cadmium-contaminated soil - Liu, Han; Li, Cui; Lin, Yang; Chen, Yi-jian; Zhang, Zhan-jiang; Wei, Kun-hua; Lei, Ming (Frontiers in Microbiology, 2024)
Excessive Cd accumulation in soil reduces production of numerous plants, such as Sophora tonkinensis Gagnep., an important and widely cultivated medicinal plant whose roots and rhizomes are used in traditional Chinese medicine. Applying a mixture of biochar and organic fertilizer was expected to improve the overall health of the Cd-contaminated soil and increase the yield and quality of Sophora. However, the underlying mechanism between this mixed fertilization and the improvement of the yield and quality of Sophora remains uncovered. This study investigated the effect of biochar and organic fertilizer applicati-on (BO, biochar to organic fertilizer ratio of 1:2) on the growth of Sophora cultivated in Cd-contaminated soil. BO significantly reduced the total Cd content (TCd) in the Sophora rhizosphere soil and increased soil water content, overall soil nutrient levels and enzyme activities in the soil. Additionally, the α diversity of soil bacteria community had been significantly improved after BO treatment. Soil pH, total Cd content, total carbon content, and dissolved organic carbon were the main reasons for the fluctuation of the bacterial dominant species. Further investigation demonstrated that the abundance of variable microorganism, including Acidobacteria, Proteobacteria, Bacteroidetes, Firmicutes, Chloroflexi, Gemmatimonades, Patescibactera, Armatimonades, Subgroups_ 6, Bacillus and Bacillus_ Acidiceler, were also significantly changed in Cd-contaminated soil. All these alternations could contribute to the reduction of the Cd content, and thus the increase of the biomass and the content of main secondary metabolites (matrine and oxymatrine) in Sophora. Our research demonstrated that the co-application of biochar and organic fertilizers has the potential to enhance soil health and increase the productivity and quality of plants by regulating the microorganisms in Cd-contaminated soil.